Pembelajaran Berdiferensiasi Metode Metakognisi Berbasis Computational Thinking Di Era Merdeka Belajar (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
This study aims to describe differentiated learning using metacognition methods based on computational thinking in the era of independent learning. The metacognition method is a learning method in which students are directed to prioritize their metacognitive abilities by using the FERA model, namely Focus, Explore, Reflex, and Apply. This model is based on constructivism theory with four stages starting from computational thinking which includes logical thinking, algorithm thinking, decomposition, pattern recognition, abstraction, modeling, and evaluation. Differentiated learning with the application metacognition method with the FERA model is very important to be applied in the free period of learning because students must be trained to focus their thinking in every situation and explore so that they are trained to be flexible in every different situation, which is a demand in a multi-problem era. This research was applied at the Potential Utama University Management Study Program in 2 classes. Class MM A Pagi as an experimental class with 30 students and class MM B Pagi as a control class with 30 students. After conducting research and evaluating by providing problems that were solved based on computational thinking, the results obtained that students' statistical abilities increased significantly. Students are very motivated during learning
Keywords: Differentiated Learning; Metacognition Method; Computational Thinking; Independent Learning